The Application and Development Trends of Wearable Devices (WD) in Endurance Sports Training: A Literature Review - Zhang, Tingran; Zhang, Mufan; Luo, Jiong (Quality in Sport, 2025)
Collecting and organizing information on the application of technology products such as wearable devices, intelligent training, and the Internet of Things (IoT) in endurance sports training from 2005 to 2023, it was found that wearable devices, heart rate bands, bicycle power devices, intelligent training device applications, and sports community platforms can be connected through the Internet of Things, and data can be automatically shared, Furthermore, provide feedback on the workload and training effectiveness of sports training; The long-distance supervision and virtual coaching system of real coaches support direct interaction between athletes and real coaches, which can promote athletes' training motivation, improve sports performance, and have a good positive effect on enhancing athletes' completion of training plans; Intelligent wearable equipment can accurately provide HR and HRV parameters, based on which training load and maximum oxygen uptake can be evaluated, providing a basis for adjusting training strategies and ensuring maximum training benefits.